Analysis of Factors Affecting Student Interest in Using Mobile Banking - Pratiwi, Novita Dea; Fariasih, Arin Fronika; Kusuma, Tyas Pratama Puja (Journal of Multimedia Trend and Technology, 2025)
Study aims to analyze the effect of trust, compatibility, perceived risk, risk acceptance, and satisfaction on students’ interest in using mobile banking applications. Mobile banking has become one of the most widely used digital financial solutions due to its convenience and practicality, especially among young users who are familiar with technology. This research employs a quantitative approach using multiple linear regression analysis. The data are derived from a secondary dataset titled “COGENT ADOPTION M-BANKING PLS,” which contains survey responses from 219 students who use mobile banking services. The analysis results reveal that satisfaction, compatibility, and trust significantly influence students’ interest in using mobile banking, while perceived risk and risk acceptance show no significant effect. The coefficient of determination (R²) value of 0.570 indicates that the model explains 57% of the variation in students’ interest in mobile banking adoption. These findings highlight the importance of user trust, system suitability, and satisfaction as key factors in sustaining mobile banking usage. The study contributes both theoretically and practically by enriching the understanding of technology acceptance behavior among students and providing insights for banking institutions to enhance application design, strengthen security systems, and develop more user-oriented mobile banking strategies.